Phosphoethanolamine cytidylyltransferase 2 integrates DAG metabolism and TBK1 activation to regulate antiviral innate immunity - Wencong Lai; Zengjie Liu; Han Hu; Wanxuan Zhang; Baolin Li; Rui Wang; Zengqi Zhao; Xueshan Li; Yihang Hu; Jinwei Duan; Dan Xu; Yongtao Liu; et al. (Proceedings of the National Academy of Sciences, 2026)
Phosphatidylethanolamine (PE) biosynthesis is critical for membrane biology and cellular homeostasis. However, its specific role in antiviral innate immunity remains poorly understood. Here, we demonstrate that inhibition of phosphoethanolamine cytidylyltransferase 2 (PCYT2), a key enzyme in PE biosynthesis, promotes TBK1 activation to enhance the antiviral innate immune response. Mechanistically, PCYT2 deficiency leads to the accumulation of diacylglycerol, which activates protein kinase C-δ (PKCδ). We identify PKCδ as a direct kinase for TBK1 and demonstrate that it binds to and phosphorylates TBK1 at Ser716. This Ser716 phosphorylation facilitates the subsequent canonical phosphorylation of TBK1 at Ser172, resulting in hyperactivation of the TBK1–IRF3 axis. Our findings uncover a link between PE metabolism and antiviral innate immunity, suggesting that targeting the PE biosynthesis pathway could be a potential therapeutic strategy against viral infections.